Mapping the gender digital divide: a bibliometric analysis of global research trends (2003–2024) - D.M. Kangalakova; S.Zh. Ibraimova; M.T. Satpayeva; T.I. Kakizhanova (Хабаршысы. Экономика сериясы)
This study aims to identify the significant contextual, evolutionary-chronological, and geographically-sectoral scientific landscape of the gender gap in digital skills through a comprehensive bibliometric analysis. The data was collected from the Scopus database using keywords such as gender, gap, digital, and skills. A total of 203 publications were identified. VOSviewer and MS Excel were used to visualize the results and display the material graphically. The study results show that Interest in the digital gender gap began in 2003; 2) the peak of the popularity of the research area occurred in 2023 when researchers published 59 publications; 3) many studies on the gender gap in the era of digitalization relate to social and computer sciences; 4) researchers from Spain and the USA have conducted the most significant studies; 5) The ratio of keywords forms 34 clusters and studies on the impact of the digital gender gap on employment, socio-economic development, and education. In addition, research trends regarding the high citation of publications have been identified. The results obtained are applicable and can guide further research on the digital gender gap.